The structural properties of chemically derived graphene nanosheets/mesophase pitch-based composite carbon fibers with high conductivities. (January 2020) - Zhang, Xingwei; Ning, Shuli; Ma, Zhaokun; Song, Huaihe; Wang, Dingling; Zhang, Man; Fan, Baolin; Zhang, Su; Yan, Xi
Abstract: A series of mesophase pitch-based composite carbon fibers with various contents of chemically derived graphene nanosheets (CGNSs) were prepared through melt-spinning, stabilization, carbonization, and graphitization. By means of scanning electron microscopy, X-ray diffraction, single-filament testing, and resistivity testing, the effect of CGNSs content on the structures and properties of the composite carbon fibers were investigated. And the thermal conductivity of the composite carbon fibers was predicted by indirect measurement. The results show that the presence of CGNSs can effectively avoid the generation of unwanted radial transverse texture and wedge cleavages of the carbon fibers prepared from pure mesophase pitch. Although the crystalline structure of CGNSs/mesophase pitch-based composite carbon fibers is not apparently improved, appropriate CGNSs content can enhance the tensile strength as well as the conductivity of the composite carbon fibers. When the CGNSs content is 0.1 wt%, the tensile strength, breaking elongation, electrical resistivity and thermal conductivity of the composite carbon fibers can attain 2.12 GPa, 0.35%, 0.95 μΩ m, and 1322 W m −1 K −1, respectively. And the successful preparation of the composite carbon fibers provides a new solution for the cost reduction of mesophase pitch-based carbon fibers with high thermal conductivity. Graphical abstract: Image 104231